Unbalance compensation for AMB systems with input delay: An output regulation approach. (January 2016) - Yoon, Se Young; Di, Long; Lin, Zongli
Abstract: Unbalance compensation is an important technique for reducing rotor vibration in high speed rotating machines caused by residual rotor unbalance. As rotating machines in remote applications aim for higher speeds to gain efficiency and to reduce footprint, there is a need to extend the unbalance compensation techniques to active magnetic bearing (AMB) systems with delays in the control loop. This paper investigates the unbalance compensation problem for AMB systems with input delays. An unbalance compensation method is developed based on a solution to the output regulator problem for systems with input delay. The proposed unbalance compensation method is verified through simulation, and experimentally validated on an AMB test rig.